HAK SIPIL AGAMA (HSA) DALAM PIAGAM MADINAH - Ichrom, Muhamad (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2020)
In this article discusses the Civil Rights of Religion (HSA). This right includes freedom to establish religion and beliefs of one's own choice, and freedom, both individually and jointly with others, both public and private, to practice their religion and beliefs in worship, observance, practice, and teaching ". It must be realized that in Islam such a thing is not absent. The Medina Charter is a strong proof of religious freedom in Islamic literature. From a comprehensive study of the Medina Charter as the constitution of the Medina state under the leadership of the Prophet Muhammad with the Hermeneutical approach found several values or principles related to religious civil rights. There are also principles that include the principles of justice, equality, freedom, and protection of minorities. These principles are the result of a dialectic between the concept of religious civil rights and the Medina Charter, one of which also includes religious freedom. There the authors find many similarities between the two. This equation can at least be seen from several things: First, that religious civil rights are rights relating to the fulfillment of rights by the state to its people relating to guarantees of freedom of religion and belief, then the Medina Charter is also a guarantee of the fulfillment of rights by the Prophet as the leader of Medina against the wrong citizens one also contains about religious freedom.